2006
DOI: 10.1007/s11103-006-9095-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis associated gene expression in maize embryos 6 days after fertilization exhibits additive, dominant and overdominant pattern

Abstract: Heterosis is important for conventional plant breeding and is intensively used to increase the productivity of crop plants. Genetic processes shortly after fertilization might be of particular importance with respect to heterosis, because coordination of the diverse genomes establishes a basis for future performance of the sporophyte. Here we demonstrate a strong crossbreeding advantage of hybrid maize embryos as early as 6 days after fertilization in a modern maize hybrid and provide the first embryo specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
98
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 44 publications
(44 reference statements)
10
98
0
3
Order By: Relevance
“…For 66% of the genes that displayed nonadditive expression in microarray experiments, this difference from additivity was confirmed in qRT-PCR experiments. This confirmation rate was similar to the values obtained for maize seedlings (Swanson-Wagner et al 2006) where among 45 genes tested in qRT-PCR 31 were confirmed to be nonadditively expressed (69%), for maize embryos where 8 of 12 (67%) nonadditively expressed genes were confirmed via qRT-PCR (Meyer et al 2007), and for shoot apical meristems where 2 of 3 genes (67%) were confirmed via qRT-PCR (Uzarowska et al 2007).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…For 66% of the genes that displayed nonadditive expression in microarray experiments, this difference from additivity was confirmed in qRT-PCR experiments. This confirmation rate was similar to the values obtained for maize seedlings (Swanson-Wagner et al 2006) where among 45 genes tested in qRT-PCR 31 were confirmed to be nonadditively expressed (69%), for maize embryos where 8 of 12 (67%) nonadditively expressed genes were confirmed via qRT-PCR (Meyer et al 2007), and for shoot apical meristems where 2 of 3 genes (67%) were confirmed via qRT-PCR (Uzarowska et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…A number of studies have compared gene expression profiles of inbred lines vs. hybrids in different maize organs and developmental stages, including embryos (Stupar and Springer 2006;Meyer et al 2007), endosperm (Guo et al 2003;Song and Messing 2003), whole seedlings (Stupar and Springer 2006;Swanson-Wagner et al 2006), immature ears (Guo et al 2006;Stupar and Springer 2006), adult leaves (Auger et al 2005), and shoot apical meristem (Uzarowska et al 2007). In addition to these studies in maize, the transcriptomes of the first Arabidopsis leaf (Vuylsteke et al 2005) and rice panicles (Huang et al 2006) have been analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations